Enhancing the eco-efficiency of concrete using engineered recycled mineral admixtures and recycled aggregates. (1st June 2020) - Franco de Carvalho, José Maria; Fontes, Wanna Carvalho; Azevedo, Carlos Felipe de; Brigolini, Guilherme Jorge; Schmidt, Wolfram; Peixoto, Ricardo André Fiorotti
Abstract: Non-conventional densely packed concrete mixtures are proposed and evaluated in this paper using engineered recycled mineral admixtures and recycled aggregates obtained from steel slag, quartz mining tailings, and quartzite mining tailings. High fines content sand-concretes containing coarser- and finer-than-cement recycled powders were designed to obtain blends with broader particle-size ranges and improved packing density. As a result, compressive strength up to 99 MPa, cement intensity up to 2.33 kg/m³/MPa, and consumption of recycled material up to 95 vol% were obtained. Compressive strengths up to 66 MPa and cement intensity up to 2.34 kg/m³/MPa were also obtained with the addition of coarse aggregates to such sand-concrete mixtures, with consumption of recycled material up to 96.5%. The results launch new insights on the role of recycled admixtures and aggregates on the mixture design of cement-based composites regarding efficiency improvement and technological performance. Highlights: A route to increase the use of residues in high eco-efficient concrete is presented. Mix designs using highly effective recycled mineral admixtures were proposed. High binder efficiencies found using the proposed techniques and materials. High strength concretes with high waste consumption were obtained. Densely packed mixtures effective in improving the waste-based concrete performance.